Efektivitas Media Berbasis Powerpoint Untuk Meningkatkan Hasil Belajar PAI Pada Siswa Kelas IX di SMP Negeri 3 Kasihan Bantul Yogyakarta - Irawan, Rohmad Devi; Dewantoro, Mohammad Hajar (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2025)
The rapid development of technology in the present era has permeated various fields, including education. In the educational field, technology can serve as a tool for learning. This greatly aids educators in fostering creativity in their teaching within the classroom. One such tool is based on powerpoint media, which is expected to enhance the learning outcomes of students. However, in reality, many educators still struggle to use or master the powerpoint media that is prevalent today. This research aims to determine the effectiveness of implementing based on powerpoint media in the Islamic Education (PAI) learning process to improve the learning outcomes of ninth-grade students at SMP N 3 Kasihan Bantul Yogyakarta. This study employs a quantitative approach with a population of 156 students, comprising all ninth-grade students from classes A to E. The sample consists of 110 students selected through random sampling. Data collection methods include questionnaires, pre-tests, and post-tests, as well as documentation. Data are analyzed using simple linear regression statistical tests. The research findings indicate that the application of powerpoint media in the Islamic Education (PAI) learning process is effective in enhancing the learning outcomes of ninth-grade students at SMP N 3 Kasihan Bantul. This is evidenced by the simple linear regression analysis, which explains that the calculated F-value (39.528) is greater than the tabulated F-value (1.92), with a significant value of 0.001, which is less than 0.05. Thus, the implementation of powerpoint media in Islamic education is effective in improving student learning outcomes.